Classroom Fatigue and Second Language Acquisition: A Study on English Learning Among Evening Class Students - Harun, Medina Yasmina; Khawas, Ursya Tiara; Kurniadiansyah, Meytha Dwi; Sentana, Yuli Mahmudah (Universitas PGRI Adi Buana Surabaya, 2025)
A considerable number of night-class students and workers encounter significant challenges related to their physical and mental well-being, which has been demonstrated to influence their motivation and focus. This study demonstrates that fatigue resulting from professional obligations leads to a significant decrease in motivation and concentration levels in students enrolled in night classes. The impact is also evident in their speaking and writing skills, attributed to the difficulty in selecting vocabulary and arranging sentences coherently when experiencing fatigue. However, listening and reading skills tend to exhibit greater stability or minimal impact. To cope with fatigue, students implement strategies such as taking brief rests, recalling academic principles, and utilizing interactive technology. Consequently, it is imperative for lecturers and institutions to implement more interactive, flexible, and relevant teaching approaches that align with real-life contexts, to assist student workers in managing fatigue and achieving optimal learning outcomes.